Difficulties in writing in vocabulary and grammar of the second year students of SMP N I Selong East Lombok West Nusa Tenggara in the school year 2008/2009 - Saiful Bahri (LPPM UNY, 2009)
This research study aims at: (1) finding out the forms of difficulties in writing in vocabulary and grammar of the second year students of SMP 1 Selong East Lombok West Nusa Tenggara in the school year 2008/2009, and (2) finding out the causal factors of difficulties in writing in vocabulary and grammar of the second year students of SMP 1 Selong East Lombok West Nusa Tenggara in the school year 2008/2009. The study was a case study. It used a qualitative positivistic descriptive approach. The participants consisted of 34 students. The main data were obtained from the 34 students compositions. The other data were collected from observation, interviews, and recording. The results show that (1) eight most common errors of students writing were: verb-tenses, articles, word forms, capital letters, punctuation, missing words, spelling, and prepositions; (2) verb-tense errors occupied the first rank (23.76%), followed by article errors (20.85%), and word form errors (10.62%); (3) two kinds of direct factors caused the students to make errors in the writing skills were: negative interlanguage and intralingual transfers in the forms of adverb interference, copulative verb interference, word-order interference, tense-form interference, overgeneralization, ignorance of rule restriction, and incomplete application of rules; and (4) five sources of indirect factors caused the students to make errors in the writing skills were: students low motivation, lack of use of media, low frequency of the writing instruction, lack of parents support, and loose control of students learning.